Symphony to perform at Shuler (Raton, NM Raton Range, 1997)
Article is about the New Mexico Symphony Orchestra coming to perform at the Shuler Theater.
Newspaper Article + Photograph of David Lockington
Master list item #: 65
File location is in the Raton file Cabinet
Keywords: Lockington, David -- Music Diector; Wood, Bill -- Composer; Green, Joseph -- Composer; New Mexico Symphony Orchestra -- Musical Group; New Mexico Arts -- Sponsor; Art and Humanities Council -- Sponsor; McCune Foundation -- Sponsor; Live Performance; Arts Promotion; Music Performance; Shuler Theater; Raton, New Mexico